The Charitable and Humanitarian Work Efforts of the Muslim World League - Alotaibi, Afaf Shaman (Politikologija religije, 2022)
The Muslim World League (MWL) is considered one of the oldest Islamic organizations that took care of charitable and relief work in the Islamic world. Over the past sixty years, it has worked to diversify its charitable, relief and humanitarian activities in line with its position as an organization in support of Muslim peoples. Besides, it has established several subsidiary organizations to handle the task of managing charitable and relief work, such as the International Commission for Relief, Welfare and Development, and the Supreme Council of Mosques, as well as other affiliated organizations that handle religious, cultural and scientific affairs. This article highlights the efforts made by the League in the health, educational, community and relief sectors, by analyzing the League's official magazine and the periodicals.